Day 3 Wed, November 11, 2020 2020
DOI: 10.2118/202895-ms
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Formulation of Novel Modified HF Acid System: Realizing Remarkable Value in Sandstone Reservoirs

Abstract: Matrix acidizing is one of the most common well stimulation methods in Malaysian brown fields. Formation damage caused by fines migration has been reported to be among the main reason for productivity decline. The need to conduct acid stimulation arises when the initial rates of the wells are below expectation or when the productivity of the reservoir drops significantly. Various mud acid formulations have been used to treat the wells from the past until recent years. However, some well treatments resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It was also discovered that although chelating agents helped to increase the permeability of the core, the HF main flush decreased the permeability due to secondary formation damage. A new chelating agent treatment combined with HF was evaluated by Mohd Jeffry et al [38] in sandstone cores. While the formulation of the chelating agent was not shown, the authors observed a 264% increase in permeability after two such treatments were used.…”
Section: Subsurface Formations Containing Sandstone Mineralsmentioning
confidence: 99%
“…It was also discovered that although chelating agents helped to increase the permeability of the core, the HF main flush decreased the permeability due to secondary formation damage. A new chelating agent treatment combined with HF was evaluated by Mohd Jeffry et al [38] in sandstone cores. While the formulation of the chelating agent was not shown, the authors observed a 264% increase in permeability after two such treatments were used.…”
Section: Subsurface Formations Containing Sandstone Mineralsmentioning
confidence: 99%